2019
DOI: 10.1080/13546783.2019.1592779
|View full text |Cite
|
Sign up to set email alerts
|

Do we make decisions for other people based on our predictions of their preferences? evidence from financial and medical scenarios involving risk

Abstract: The ways in which the decisions we make for others differ from the ones we make for ourselves has received much attention in the literature, although less is known about their relationship to our predictions of the recipient's preferences. The latter question is of particular importance given real-world occurrences of surrogate decision-making which require surrogates to consider the recipient's preferences. We conducted three experiments which explore this relationship in the medical and financial domains. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Contrary to our expectations, we did not find that any of our measures related to mortality had an effect on participants’ propensity to accept life-saving treatment, neither for themselves nor for their partner. This is consistent with Batteux et al, 13 who found that surrogates reported similar wishes and decision processes despite large variabilities in their propensity to accept life-saving treatment. More research is therefore needed to understand this variability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Contrary to our expectations, we did not find that any of our measures related to mortality had an effect on participants’ propensity to accept life-saving treatment, neither for themselves nor for their partner. This is consistent with Batteux et al, 13 who found that surrogates reported similar wishes and decision processes despite large variabilities in their propensity to accept life-saving treatment. More research is therefore needed to understand this variability.…”
Section: Discussionsupporting
confidence: 90%
“…11,12 On the other hand, in a within-subjects design, we found that surrogate predictions were significant predictors of surrogate choices, independently of the decision maker’s own choices. 13 This suggests that surrogates do not simply disregard the recipient’s preferences but are influenced by other factors.…”
mentioning
confidence: 99%
“…This is also supported by findings in the medical domain, where people accept less risk for others (Batteux, Ferguson, & Tunney, 2019a;Polman & Wu, 2020). These show that, for others, people are more likely to choose a treatment to avoid a painful or deadly illness (Batteux, Ferguson, & Tunney, 2019c;Garcia-Retamero & Galesic, 2012), while also more likely to refuse a treatment involving a risk of death (Batteux, Ferguson, & Tunney, 2019b).…”
supporting
confidence: 63%
“…Our second aim was to test whether the cautious shift account applies to significant financial decisions, as in medical decisions (Batteux et al, 2019b). This does not seem to be the case.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, discrepancies have been found between surrogate choices and predictions. Surrogates avoid a risk of death for someone else more than themselves, despite predicting that they have similar preferences [22][23][24]. This suggests that surrogates override the recipient's preferences to make a more cautious decision on their behalf which preserves their chances of living.…”
Section: How Do Surrogates Make Decisions?mentioning
confidence: 99%